2008
DOI: 10.1177/1077801208321987
|View full text |Cite
|
Sign up to set email alerts
|

Gender Attitudes and Sexual Behaviors

Abstract: This research examines the impact of participating in different sports on male athletes' gender attitudes, hegemonic masculinity, sexual behavior, and sexual aggression. Expanding on past research that compares athletes with nonathletes, this research finds differences between collegiate athletes and men who do not participate in collegiate sports, as well as between men who play different collegiate sports. Athletes in center sports (such as football) scored significantly higher on hyper-masculinity scales, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 18 publications
0
62
0
Order By: Relevance
“…In addition to the importance of reducing the prospect of violence outside of the playing fields, these types of interventions are important because even though our study's results suggested that football players are relatively comfortable expressing affection toward other men within the football environment, many scholars (e.g., Gage, 2008;Messner, 1990Messner, , 1992Messner, , 2002Pringle & Markula, 2005) have acknowledged the prevalence of homophobia in sport, particularly in contact sports like football. Football provides an interesting environment wherein certain displays of affection may be considered unacceptable, yet other man-on-man affectionate acts are allowed and deemed appropriate in particular situations (e.g., celebrating a good play).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to the importance of reducing the prospect of violence outside of the playing fields, these types of interventions are important because even though our study's results suggested that football players are relatively comfortable expressing affection toward other men within the football environment, many scholars (e.g., Gage, 2008;Messner, 1990Messner, , 1992Messner, , 2002Pringle & Markula, 2005) have acknowledged the prevalence of homophobia in sport, particularly in contact sports like football. Football provides an interesting environment wherein certain displays of affection may be considered unacceptable, yet other man-on-man affectionate acts are allowed and deemed appropriate in particular situations (e.g., celebrating a good play).…”
Section: Discussionmentioning
confidence: 96%
“…A center sport such as football is likely to maintain its position of privilege on campus by receiving preferential institutional interest, greater financial resource allocation, and more media attention. Subsequently, this sustained level of preferential treatment can contribute to an environment that perpetuates the superiority of traditional masculine gender ideologies within this sport (Gage, 2008). As a center sport, football is seen as an influential agent of socialization for new generations of young men, while also serving to maintain the traditional values of the previous generation of men (Foley, 2001).…”
Section: Masculinity Within Sporting Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Football is a sport that teaches its players how to be violent and aggressive on the field (Gage, 2008;Messner, 1990), but little research has addressed if players learn to compartmentalize this instrumental aggression and deem it to be appropriate only on the field.…”
Section: Resultsmentioning
confidence: 99%
“…This pressure to conform to team norms of masculinity may contribute to aggressive behavior off the field (Curry, 2000). "Reinforcement of masculine gender norms through strict football rituals in team practice creates a behavioral repertoire that may extend to other contexts, with gender norms also informing the interpersonal relationships that athletes form off the field" (Gage, 2008(Gage, , p. 1016.…”
Section: Masculinity Norms and Sport Participationmentioning
confidence: 99%